Pengaruh Kedalaman Terendam Disk Pada Proses Rotary Alga Biofilm Reactor Menggunakan Mikroalga Chlorella SP. Untuk Penyisihan COD, TSS Limbah Cair Domestik - Mardhatillah, Annisa; Elystia, Shinta; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic wastewater consists of black water and grey water, grey wateras the largest contributor to the total domestic wastewater contains organicmaterial. Microalgae Chlorella sp can its organic compounds and nutrients forphotosynthesis to reduce pollutants in grey wastewater. Rotary Algae BiofilmReactor (RABR) technology is a biological treatment with a suspended growthsystem and uses disk media as a site for attached growth occurs. This study aims to remove COD and TSS parameters in grey waste water by treatment withvariations in depth of immersed disks, which are 40%, 60%, and 80% in contact0,1,3, and 5 days. The results of the highest research during the deep processing showed the efficiency parameters, namely the variation of the depth of the disk submerged 80% on day 5 with the total density of microalgae cells Chlorella sp. suspension-based and attached at 9,55 x 106 cells/ml. The removal efficiency of COD was 81,58% with a concentration of 100 mg/l and the increase in TSS concentration was 522 mg/l.Key Word : Rotary Alga Biofilm Reactor (RABR), Grey Waste Water, Chlorellasp., Depth of Immersed Disk, COD.